Análise da robustez e aplicações de controle com modos deslizantes em sistemas incertos com atraso no controle - Garcia, Saulo Crnkowise [UNESP] (2014)
This work deals with control of uncertain systems with sliding modes. The main focus of the contributions is given in the investigation of this method of control accomplished via communication network subject to time delay. To minimize the degenerative effects of delay, state predictors in its simpler format is used in the control law. Analyses of the stability robustness are made and also analyses about the influence that the uncertainties and delay exert on the behavior of closed-loop systems. To corroborate the results presented in the analyses, simulations are performed on a mathematical model of a system of order two, in a linear model of the active suspension system and a nonlinear model of the inverted pendulum system. In this last, the delay is treated as a failure and a strategy to detect and adapt the controllers to this type of failure is presented. Through simulations, sliding mode control in two processes of the primary oil treatment is also investigated